India’s Neighborhood First Policy in South Asia: : Revisiting its Implications in Post-Hasina Regime - Uddin, Md. Shihab; Tabassum, Anika; Hasan, Kamrul (The Jahangirnagar Review, 2025)
India’s ‘Neighborhood First’ policy aims to strengthen ties with South Asian nations, particularly Bangladesh, which is close by and has historical, religious, and cultural ties with India. This policy seeks to promote mutual security, economic cooperation, and regional peace. Both nations have a large number of MoUs, agreements, training and exchange programs for civil-military bureaucrats, significant trade flow, and border control accomplishments. The bilateral relations between Bangladesh and India are often termed as the highest level of friendly relationship by politicians from both sides. However, diplomatic relations have seriously been disrupted by the mass uprising in 2024, frequently dubbed as Bangladesh Revolution or Bangladesh 2.0, resulting in a new border dispute, heated speech by both sides, breakdown of usual trade relations, disinformation propagated by India against Bangladesh, water-sharing problems, and mistrust. Furthermore, the normalization and deepening of bilateral ties between Bangladesh and Pakistan and China’s increasing influence in Bangladesh via investments and strategic alliances further complicate the regional dynamic. Against this backdrop, this paper revisits the BJP government’s ‘Neighborhood’ first policy, critically evaluating the bilateral ties, including trade, diplomacy, indiscriminately killing of Bangladeshi nationals by Indian BSF at Bangladesh-India border, water conflict, flash floods, and so on. Drawing on the descriptive method, this paper is predominantly based on secondary literature, which includes journal articles, government documents, statements by political leaders and bureaucrats, newspaper articles, etc. Besides the introduction in section one, the article briefly discusses the bilateral relations in section two, while section three explores the ‘Neighborhood First’ policy. The paper then evaluates the bilateral ties in section four, revisiting the ‘Neighborhood First’ policy, and finally, section five concludes the paper with policy recommendations.